Competencies Needed for Improving Teaching Among Lecturers of Polytechnics in North-Western Nigeria - Yusof, Yusmarwati; Ibrahim Haruna Bako, Ibrahim Haruna Bako; Roddin, Rohayu; Marina Ibrahim Mukhtar, Marina Ibrahim Mukhtar; Hamid, Hashima (uthm, 2023)
The study was carried out to determine the competencies needed for improving teaching among lecturers of polytechnics in North-western Nigeria. A polytechnic was established in Nigeria to train individuals to learn a specific skill using competent lecturers for employment or self-reliance after graduation. These lecturers are very essential to the quality of students of electrical/ electronic technology in the polytechnics. However, technology dynamism has become a serious challenge for the lecturers to perform their teaching tasks. Hence the need for lecturers to continually improved on their competence and knowledge of the subject matter content they teach. The study is also to identify any difference of competency needed among the institutions. 122 electrical/electronic lecturers from nine universities were purposely selected as respondents for the study whose consisted of 55 lecturers from five state polytechnics and 67 lecturers from four federal polytechnics. The study adopted survey research design and used structured questionnaire as the main instrument for the data collection. The questionnaires were developed and distributed to respondents. Mean and improvement needed index analysis were used for data analysis to achieve the research objective whilst t-test was used to test the significance difference between the institutions. It was found that electrical/electronic lecturers in polytechnics need improvement of their competencies related to knowledge and skills in the subject matter. However, there was no significant difference of competency needed between the lecturers in state and federal polytechnics on the teaching subject matter. The implication of the finding is that the location of the lecturers did not significantly affect their opinion in the competencies. In conclusion, lecturers of electrical/electronic technology from the polytechnics has low competency in executing technical task assigned to them within the study area which required adequate investigation by determining the competencies of lecturers who happen to be the main implementers of the electrical/electronic programme. Therefore, it is recommended that the schools administrators should continually organized workshop and training for lecturers to build their capacity in order for the lecturers to always develop their competencies to effectively teach the contents of the subject assigned to them.